Engagement of Academic Staff Amidst COVID-19: The Role of Perceived Organisational Support, Burnout Risk, and Lack of Reciprocity as Psychological Conditions - van der Ross, Melissa Reynell; Olckers, Chantal; Schaap, Pieter (Frontiers in Psychology, 2022)
The COVID-19 crisis has resulted in radical changes within the higher education system, requiring academia to rapidly transition from the traditional learning model to a distance or blended model of learning to ensure continuity of educational processes. These changes have placed additional demands on academic staff who already have a heavy workload. According to the job demands-resources model, these additional demands may have an impact on the burnout risk, engagement, and well-being of academic staff. In alignment with the premises of positive psychology the primary objective of this study was to explore the interplay of three psychological conditions (meaningfulness, safety, and availability) needed to stimulate engagement. To investigate this interplay, the researchers connected Kahn’s theory on engagement with current concepts that focus on the person-role relationship, such as those dealt with in the job demands-resources model, organisational support theory, and perceptions of reciprocity. Mediating effects between burnout risk, engagement, and psychological well-being, as well as the moderating effect of lack of reciprocity, were tested using structural equation modelling. The study used a purposive, non-probability sampling method and a cross-sectional survey research design. Participants were 160 academic staff members employed at a university in South Africa. The findings of this study revealed that the three psychological conditions (meaningfulness, safety, and availability), which were operationalised as lack of reciprocity, perceived organisational support, and burnout risk, were significantly related to emotional engagement. Perceived organisational support (job resources), which met the criteria for psychological safety and some components of meaningfulness, displayed the strongest association with engagement. Policymakers within higher education institutions should be sensitive to the issues this study focused on, especially as regards the need to provide organisational support in times of crisis, such as the COVID-19 pandemic.